Phase 2 Study of Adjuvant Radiotherapy Following Narrow‐Margin Hepatectomy in Patients With HCC. Issue 5 (16th September 2021) - Chen, Bo; Wu, Jian‐Xiong; Cheng, Shu‐Hui; Wang, Li‐Ming; Rong, Wei‐Qi; Wu, Fan; Wang, Shu‐Lian; Jin, Jing; Liu, Yue‐Ping; Song, Yong‐Wen; Ren, Hua; Fang, Hui; et al.
Abstract : Background and Aims: Surgical resection is the primary treatment for HCC; however, it is associated with a high rate of recurrence and death. We conducted this phase 2 study to investigate the efficacy and safety of postoperative intensity‐modulated radiotherapy (IMRT) for HCC after narrow‐margin hepatectomy. Approach and Results: We designed a single‐arm, prospective phase 2 trial to evaluate overall survival (OS), disease‐free survival (DFS), recurrence patterns, and toxicity in patients receiving adjuvant radiotherapy. The eligibility criteria included the following: pathological diagnosis of HCC after hepatectomy, with narrow pathological margins (< 1 cm); age > 18 years; and Eastern Cooperative Oncology Group performance status score of 0 or 1. Patients received IMRT within 4‐6 weeks after surgical resection. This trial was registered at ClinicalTrials.gov (NCT01456156). Between 2008 and 2016, a total of 76 eligible patients who underwent narrow‐margin resection were enrolled. The median follow‐up duration was 70 months; the 3‐year OS and DFS rates were 88.2% and 68.1%, respectively; and the 5‐year OS and DFS rates were 72.2% and 51.6%, respectively. Intrahepatic recurrence was the primary recurrence pattern. No marginal recurrence was found. Intrahepatic, extrahepatic, and combined recurrences at the first relapse were found in 33, 5, and 1 patient, respectively. The most common radiation‐related grade‐3 toxicities were leukopenia (7.9%), elevated alanine aminotransferase (3.9%) and aspartate aminotransferase (2.6%) levels, and thrombocytopenia (1.3%). Classical or nonclassical radiation‐induced liver disease was not noted. Conclusions: Adjuvant radiotherapy is an effective, well‐tolerated, and promising adjuvant regimen in patients with HCC who have undergone narrow‐margin hepatectomy. Our trial provides evidence and a rationale for planning a future phase 3 trial.